Serious Crime in China. - Trevaskes, Susan (Routledge studies on China in transition., 2012)
Despite a resurgence in the number of studies of Chinese social control over the past decade or so, no sustained work in English has detailed the recent developments in policy and practice against serious crime, despite international recognition that Chinese policing of serious crime is relatively severe and that more people are executed for crime in China each year than in the rest of the world combined. In this book the author skilfully explores the politics, practice, procedures, and public perceptions of policing serious crime in China, focusing on one particular criminal justice.